PENDIDIKAN DAN PERNIKAHAN DINI STUDI KASUS DI DESA PARANGLOMPOA KABUPATEN GOWA MAKASSAR. - Basmawati; Amos Neolaka (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2018)
This study aims to find out the education of schools in the village of Paranglompoa, education of children in the family, community education in the village Paranglompoa, and to know the understanding of early marriage in the village Paranglompoa. The research was conducted in Paranglompoa village of Gowa Makassar district in February-March 2018 using survey method with qualitative descriptive approach and phenomenology approach. In the data collection is through observation, interview and documentation. Selection of informants using purposive sampling technique (sample aims) is the informants that researchers set as many as 20 people consisting of the community, parents, teachers, students and perpetrators of early marriage. Discussion in this research there are 4 sub focus that is school education, family education, community education and understanding of early marriage. The results of the study note that the dropout of education and the occurrence of early marriage is caused by the low level of parental education, economically weak, pregnancy outside marriage, the distance between parents and children far apart where children raised by grandmother, while the parents wander into Indonesian workers in Malaysia and caused because lack of understanding of the community early-age marriage. The challenge faced by the local village is the lack of character education for the local people. The solution provided that the community needs to be embraced, and invited cooperation in terms of continuation of children's education, community education and the importance of understanding early marriage. So that the number of school dropouts and early marriage can be avoided.